A Structural Equation Model of Causal Factors Influencing Teachers’ Instructional Management in the Thonburi University School Network, Thailand - Kongkachat, Sudarat; Thespluem, Marisa; Yamchuti, Nophawan; Chaoranong, Chaiyot; Jungate, Phairat (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study aimed to examine a structural equation model of causal factors influencing teachers’ instructional management and to investigate guidelines for promoting instructional management among teachers in the Thonburi University school network. The study employed a mixed-methods research design, incorporating both quantitative and qualitative approaches. The sample consisted of 392 teachers selected through cluster random sampling. The research instruments consisted of a questionnaire with a reliability coefficient of 0.97 and an interview protocol that had been validated for content validity, with a content validity index (IOC) of 1.00. Quantitative data were analyzed using descriptive statistics and partial least squares structural equation modeling (PLS-SEM), while qualitative data were analyzed using content analysis.           The findings revealed that the structural equation model demonstrated a good fit with the empirical data and explained a high proportion of variance in teachers’ digital literacy and instructional management. Teachers’ digital literacy exerted the strongest direct effect on instructional management and served as a key mediating variable between organizational contextual factors and instructional management. In addition, the proposed guidelines emphasized the development of supportive school environments and learning-oriented organizational cultures, together with the enhancement of digital literacy among teachers and students, to promote learner-centered instructional management aligned with societal changes and future labor market demands. These findings indicate that improving teachers’ instructional management within school network contexts should be primarily driven by strengthening teachers’ digital literacy as a core mechanism.